2023
DOI: 10.1590/fst.121622
|View full text |Cite
|
Sign up to set email alerts
|

Volatile metabolite profiling of linolenic acid oxidation in the heating process

Abstract: Linolenic acid is an important fatty acid, and volatiles generated by its oxidation are the major components of food flavor. In this study, volatile components generated from linolenic acid during heating were detected and analyzed by using thermal desorption cryo-trapping system coupled with gas chromatography-mass spectrometry. A total of 52 volatile compounds were identified, including aldehydes (18), ketones (12), alcohols (6), furans (4), acids (6) and aromatic compounds (6). The forming temperature of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Moreover, 2‐ethylfuran has been considered to contribute to the distinct sardine‐fishy odor (Prost et al., 2004). Liu, Lin, Don and Dong (2023) observed that 2‐pentylfuran can be generated through heat oxidation of linoleic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 2‐ethylfuran has been considered to contribute to the distinct sardine‐fishy odor (Prost et al., 2004). Liu, Lin, Don and Dong (2023) observed that 2‐pentylfuran can be generated through heat oxidation of linoleic acid.…”
Section: Resultsmentioning
confidence: 99%